2005
DOI: 10.1074/jbc.m409442200
|View full text |Cite
|
Sign up to set email alerts
|

The Promyelotic Leukemia Zinc Finger Promotes Osteoblastic Differentiation of Human Mesenchymal Stem Cells as an Upstream Regulator of CBFA1

Abstract: Ossification of the posterior longitudinal ligament of the spine (OPLL) is the leading cause of myelopathy in Japan and is diagnosed by ectopic bone formation in the paravertebral ligament. OPLL is a systemic high bone mass disease with a strong genetic background. To detect genes relevant to the pathogenesis of OPLL, we performed a cDNA microarray analysis of systematic gene expression profiles during the osteoblastic differentiation of ligament cells from OPLL patients (OPLL cells), patients with a disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 43 publications
7
78
0
1
Order By: Relevance
“…Small interfering RNA knockdown of ZBTB16 in human and mouse MSC reduced osteogenic differentiation and expression of collagen 1A1 (COL1A1), alkaline phosphatase, RUNX2, and OC. Furthermore, overexpression of Zbtb16 in a murine MSC line increased Runx2 and Col1A expression during osteogenic differentiation [39]. Collectively, these studies and this current study have identified ZBTB16 as a regulator of osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Small interfering RNA knockdown of ZBTB16 in human and mouse MSC reduced osteogenic differentiation and expression of collagen 1A1 (COL1A1), alkaline phosphatase, RUNX2, and OC. Furthermore, overexpression of Zbtb16 in a murine MSC line increased Runx2 and Col1A expression during osteogenic differentiation [39]. Collectively, these studies and this current study have identified ZBTB16 as a regulator of osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 52%
“…ZBTB16 has previously been implicated in regulating osteogenesis in human MSC by acting upstream of RUNX2 to promote osteogenic differentiation and the expression of key osteogenic differentiation genes [38,39]. However, the direct role of MX1 and FHL1 in regulating MSC osteogenic differentiation is not as well defined.…”
Section: Targeted Knockdown Of Mx1 and Fhl1 Inhibits Msc Osteogenic Dmentioning
confidence: 89%
See 1 more Smart Citation
“…The expression of ZBTB16 was previously reported in DFCs induced with dexamethasone but not in BMP2-or IGF2-differentiated cells [20,24]. ZBTB16 was reported as an inducer of osteoblast-like and osteoblast cell differentiation and mineralization acting upstream of RUNX2 independent but very closely related to the BMP-signaling pathway, [47,48]. Interestingly, ZBTB16, RUNX2, and ALP were up-regulated while BSP was downregulated after DLX3 overexpression.…”
Section: Figmentioning
confidence: 67%
“…In particular, previous studies by our group demonstrate that Goα regulates PKA signaling and increases the number of newly formed neurites [3,4], supporting its role as an activator of neuronal differentiation. PLZF induces cell differentiation in megakaryocytes [42], osteoblasts [43], and neurons [44]. Activation of CB also promotes neuronal differentiation [13,45].…”
Section: Discussionmentioning
confidence: 99%